The neural basis of fatigue - Gandevia, S. (1999)
This review considers some of the adaptations which take place in the central nervous system to allow optimal performance of the musculoskeletal system for the smallest to the largest "efforts". Mental imagery of exercise helps performance but the way in which it works are multifactional: it evokes muscle contraction sufficient to activate muscle receptors. Furthermore, it is possible for subjects to focus specifically on control of particular muscles even without feedback from them. On the other hand maximal voluntary efforts, at least in isometric and in concentric contractions, can drive the motoneurones sufficiently to ensure full force production by the muscle. Many neural factors contribute to maintain force output during repetitive activity, including a feedback loop whereby increased central command during fatigue acts to enhance muscle perfusion. As peripheral muscle fatigue develops, changes occur in the excitability of the motor cortex. Recent evidence suggests that "central" factors leading to reduced drive to muscles in isometric contractions act "upstream" of motor cortical output.